Crystalline-amorphous heterogeneous P-CeO2 with hollow shell-shell structure as well as preparation method and application of crystalline-amorphous heterogeneous P-CeO2

Through the crystallization-amorphous heterogeneous P-CeO2 material modified separator of hollow shell-shell structure, the problem of polysulfide diffusion in lithium-sulfur batteries is solved, the electrochemical performance and cycle stability of the battery are significantly improved, and high efficiency is achieved polysulfide conversion and inhibition.

CN119284938APending Publication Date: 2025-01-10SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411388934.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The "shuttle effect" of polysulfides in lithium-sulfur batteries leads to a decline in electrochemical performance. The existing separators cannot effectively inhibit their diffusion, affecting the cycle life of the battery and the efficiency of the Coulomb.

Method used

The hollow shell-shell structure crystalline-amorphous heterogeneous P-CeO2 material was used as the modified material for lithium-sulfur battery separator. The hollow structure cerium oxide CeO2 was synthesized through Cu2O template and sodium thiosulfate etchant, and passed twice. Phosphate curing preparation forms a multi-shell structure of a highly crystalline CeO2 inner shell and amorphous CePO4 outer shell, providing catalytic sites and physical barriers.

Benefits of technology

It effectively inhibits the diffusion of polysulfides, improves the electrochemical performance of lithium-sulfur batteries, significantly improves the cycle stability and rate performance, increases the sulfur utilization rate, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284938A_ABST
    Figure CN119284938A_ABST
Patent Text Reader

Abstract

The invention discloses a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure and a preparation method and application thereof, the method comprises the following steps: step 1, firstly dissolving polyvinylpyrrolidone in an ethanol solution, then adding CeCl3. 7H2O, after the CeCl3. 7H2O is dissolved, then adding Cu2O, and stirring at room temperature to obtain a brick red solution; step 2, dropwise adding a sodium thiosulfate solution into the brick red solution to obtain a faint yellow solution, stirring at room temperature, and then sequentially standing, aging, centrifuging, washing and vacuum drying to obtain light yellow hollow CeO2 powder; step 3, weighing the hollow CeO2 powder and NaH2PO2.H2O, putting the hollow CeO2 powder and NaH2PO2.H2O into a tubular furnace, and carrying out heat preservation for 2-5 hours at the temperature of 300-600 DEG C in an argon atmosphere to obtain an intermediate product; and step 4, weighing the intermediate product and NaH2PO2.H2O, putting the weighed intermediate product and NaH2PO2.H2O into a tubular furnace, and carrying out heat preservation for 2-5 hours in an argon atmosphere at 300-600 DEG C to obtain the crystalline-amorphous heterogeneous P-CeO2 with the hollow shell-shell structure, so that the shuttle effect of polysulfide can be effectively inhibited, and the electrochemical performance of the lithium-sulfur battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-sulfur batteries, and in particular is a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure, and a preparation method and application thereof. Background Art

[0002] As a new type of energy storage system, lithium-sulfur battery (Li-S) has a theoretical capacity of up to 1675mAh / g and a theoretical mass energy density of up to 2600Wh / kg. Moreover, elemental sulfur is abundant in reserves, low in cost, environmentally friendly, safe and reliable. Therefore, lithium-sulfur battery is considered to be the next generation of battery energy storage equipment with great application prospects. However, there are still some bottleneck problems to be solved in the development of lithium-sulfur battery, such as poor conductivity of cathode material S, "shuttle effect" of polysulfides (LiPSs), and volume expansion of electrodes during charging and discharging. Among them, the most serious and urgent problem to be solved is the "shuttle effect" of polysulfides. The elemental sulfur cathode forms soluble polysulfide intermediates during charging and discharging. The polysulfides diffuse in the electrolyte to the lithium negative electrode and continuously deposit on the surface of the lithium negative electrode, thereby increasing the internal impedance of the battery and sharply reducing the electrochemical performance. Therefore, inhibiting the "shuttle effect" of polysulfides becomes the key to improving the comprehensive performance of Li-S batteries.

[0003] The diaphragm is an indispensable component of lithium-sulfur batteries. It can not only effectively provide a lithium ion diffusion path, but also physically separate the positive and negative electrodes to prevent short circuits. It can also regulate the transmission behavior of lithium ions, guide the deposition of lithium, prevent the growth of lithium dendrites, and improve battery stability. Lithium-sulfur batteries commonly use single-layer polypropylene PP diaphragms. Since the pore size of the PP diaphragm is much larger than the diameter of the polysulfide molecules, the PP diaphragm cannot hinder the diffusion of polysulfides inside the battery. Therefore, the diaphragm is usually optimized to inhibit the diffusion of polysulfides to the lithium negative electrode side, so as to improve the cycle life of the battery and increase the coulombic efficiency of the battery. In the common diaphragm optimization methods, either an intermediate layer is added between the diaphragm and the battery, or a tightly connected functional material layer is formed by growth, coating and filtration on the diaphragm surface.

[0004] Polar catalytic materials are helpful for chemical anchoring and accelerating the kinetic conversion of LiPSs. Polar crystalline materials have high structural anisotropy and saturated coordination configuration, and their surface catalytic effect is often not ideal. On the contrary, polar amorphous compounds have short-range ordered structures, unsaturated coordination environments, abundant defects and even dangling bonds, which can easily provide abundant catalytic active sites for the realization of surface and bulk electrocatalysis, which is beneficial to the robust anchoring of LiPSs and accelerated catalytic conversion, for example: [J.Yu, J.Xiao, A.Li, Z.Yang, L.Zeng, Q.Zhang, Y.Zhu, L.Guo, Enhanced Multiple Anchoring and Catalytic Conversion of Polysulfides by Amorphous MoS3Nanoboxes for High-Performance Li-S Amorphous CoPnanoparticle composites with nitrogen-doped hollow carbon nanospheres for synergetic anchoring and catalytic conversion of polysulfides in Batteries, Angew. Chem. Int. Ed. 59 (31) (2020) 13071-13078.] was reported as an advanced sulfur host. The strong chemical interaction between unsaturated Mo and lithium polysulfides effectively alleviated the shuttle effect. The catalytic effect of MoS3 improved the redox reaction kinetics. Moreover, the flexible amorphous material with hollow porous structure has a large tolerance to volume change and high sulfur loading. The amorphous NC / MoS3 nanobox enables the sulfur electrode to have high area capacity, excellent rate capacity and good cycle stability; [W. Zhou, D. Zhao, Q. Wu, B. Fan, J. Dan, A. Han, L. Ma, X. Zhang, L. Li, Amorphous CoPnanoparticle composites with nitrogen-doped hollow carbon nanospheres for synergetic anchoring and catalytic conversion of polysulfides in Li-Sbatteries, J.Colloid Interface Sci.603 471(2021)1-10.] synthesized amorphous CoP / HCS anchored on N-doped carbon nanospheres by a surface pyrolysis method. As a superior sulfur host, the strong chemical anchoring effect between unsaturated Co and lithium polysulfide, as well as the remarkable adaptability of the hollow porous structure to volume changes, help to achieve ultra-long life cycle stability, and the amorphous CoP nanoparticles not only catalyze the conversion of lithium polysulfide as an electrocatalyst, but also obtain high sulfur loading as a sulfur host material; [R.Sun, Y.Bai, M.Luo, M.Qu, Z.Wang, W.Sun, K. Sun, Enhancing Polysulfide Confinement and Electrochemical Kinetics by Amorphous Cobalt Phosphide for Highly Efficient Lithium-Sulfur Batteries, ACS Nano 15(1)(2020) 739-750.] Amorphous cobalt phosphide grown on reduced graphene oxide-multi-walled carbon nanotubes (rGO-CNT-CoP(a)) was used as a sulfur host to study the differences in adsorption and conversion between amorphous cobalt phosphide (CoP) and crystallized cobalt phosphide (CoP) on the surface of lithium polysulfides (LiPSs). Amorphous CoP not only enhanced the chemical adsorption of LiPSs, but also greatly accelerated the liquid phase conversion of LiPSs and the nucleation and growth of Li2S. In addition, amorphous CoP has higher binding energy and lower diffusion energy barrier for LiPSs, and its energy gap is reduced. The electron concentration of adsorbed LiPSs near the Fermi level is increased, which helps to improve the chemical adsorption capacity and accelerate the redox kinetics. .

[0005] Studies have found that highly crystalline-amorphous heterostructures with shell-shell structures can actively coordinate their respective advantages, optimize the absorption / desorption of polysulfur intermediates, and achieve synergistic effects in catalytic conversion, such as [L. Guo, J. Xie, S. Chen, Z. He, Y. Liu, C. Shi, R. Gao, L. Pan, Z.-F. Huang, X. Zhang, J.-J. Zou, Self-supported crystalline-amorphous composites of metal phosphate and NiS for high-performance water electrolysis under industrial conditions, Appl. Catal., B 340(2024)123252.] proposed a simple and mild method to construct a crystalline-amorphous composite of metal phosphate (MPi) and NiS on nickel foam (NF) for practical water electrolysis. The composite can be in situ converted into highly active and targeted species at high current density. It has a unique pore structure connected by nanosheets, which provides abundant catalytic sites and open channels for efficient bubble diffusion; [X.-Z. Song, W.-Y. Zhu, J.-C. Ni, Y.-H. Zhao, T. Zhang, Z. Tan, L.-Z. Liu, X.-F. Wang, Boosting Hydrogen Evolution Electrocatalysis via Regulating the Electronic Structure in a Crystalline-Amorphous CoP / CeO x p-n Heterojunction, ACS Appl. Mater. Interfaces 14(29)(2022)33151-33160.] x Successfully combined with p-type CoP to form CoP / CeO x The pre-designed Co(OH)2 / CeO heterojunction was synthesized by the developed reductive hydrolysis strategy. x Phosphorylation to prepare crystalline-amorphous CoP / CeO x Heterojunction, pn CoP / CeO x The heterojunction has a strong built-in potential of 1.38 V, which can tune the electronic structure of the active CoP in the space charge region, enhance its intrinsic activity, and promote electron transfer.

[0006] In summary, it is expected to design and develop a highly crystalline-amorphous heterostructure material with a shell-shell structure suitable for Li-S batteries, which can be used to optimize the modified lithium-sulfur battery separator and then inhibit the "shuttle effect" of polysulfides to improve the comprehensive performance of Li-S batteries. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure and a preparation method and application thereof. P-CeO2 can effectively inhibit the "shuttle effect" of polysulfides and improve the electrochemical performance of lithium-sulfur batteries.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] A method for preparing crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure comprises the following steps:

[0010] Step 1: Dissolve 10-40 g of polyvinyl pyrrolidone in 600-800 mL of 50% ethanol solution, add 300-600 mg of CeCl3·7H2O, and after it is dissolved, add 300-600 mg of Cu2O, stir at room temperature, and obtain a brick red solution;

[0011] Step 2, 200-400 mL of 1M sodium thiosulfate solution was added dropwise to the brick-red solution to obtain a light yellow solution, which was stirred at room temperature, and then allowed to stand for aging, centrifuged, washed and vacuum dried in sequence to obtain a light yellow hollow CeO2 powder;

[0012] Step 3, weighing hollow CeO2 powder and NaH2PO2·H2O in a mass ratio of 1:20 and placing them at both ends of a porcelain boat respectively, placing the porcelain boat into a tube furnace, and heating from room temperature to 300-600°C at a heating rate of 2°C / min under an argon atmosphere, and keeping the temperature for 2-5h to obtain an intermediate product;

[0013] Step 4. Weigh the intermediate product and NaH2PO2·H2O in a mass ratio of 1:20 and place them at both ends of a porcelain boat respectively. Put the porcelain boat into a tubular furnace. In an argon atmosphere, heat the temperature from room temperature to 300-600°C at a heating rate of 2°C / min and keep it warm for 2-5h to obtain a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure.

[0014] Furthermore, the Cu2O in step 1 is prepared by the following method:

[0015] Step 1.1, mixing ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution;

[0016] Step 1.2, in a water bath at 50-80°C, first dissolve 1-4 g of Cu2SO4·5H2O in 100-300 mL of the ethanol solution prepared in step 1.1, then add 10-30 mL of ethylene glycol, stir for 40 min, then add 5-20 mL of 2M NaOH solution dropwise, stir for 40 min, to obtain a black solution;

[0017] Step 1.3, add 3-10 g of ascorbic acid powder into 30-50 mL of ultrapure water and stir for 40 min to obtain an ascorbic acid solution;

[0018] Step 1.4: Add ascorbic acid solution dropwise to the black solution to obtain a brick-red solution. Stir the solution at room temperature for 40 min, let it stand for 3 h, and then filter, wash and vacuum dry in sequence to obtain brick-red Cu2O.

[0019] Furthermore, the stirring in step 1 is carried out using a magnetic stirrer for 30 minutes.

[0020] Furthermore, the stirring time of step 2 is 1 h.

[0021] Furthermore, the static aging time in step 2 is 12 hours.

[0022] Furthermore, the washing in step 2 is performed by alternately washing with deionized water and anhydrous ethanol for 3 times.

[0023] Furthermore, the vacuum drying in step 2 is performed in a vacuum drying oven at 60° C. for 12 hours.

[0024] A crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure.

[0025] Application of a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure in lithium-sulfur battery separators.

[0026] Furthermore, the application of the crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure in a lithium-sulfur battery separator comprises the following steps:

[0027] The crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure, acetylene black and PVDF were weighed and mixed in a mass ratio of 8:1:1, and then NMP was added dropwise and stirred to obtain a uniform slurry. The slurry was evenly coated on the surface of a commercial polypropylene separator and dried to obtain a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure modified lithium-sulfur battery separator.

[0028] Compared with the prior art, the present invention has the following technical effects:

[0029] The present invention is based on the Pearson hard-soft acid-base theory. First, Cu2O is used as a template and sodium thiosulfate Na2S2O3 is used as an etchant to synthesize hollow-structured cerium oxide CeO2. Then, through two phosphating curing processes, a crystalline-amorphous heterogeneous P-CeO2 material with a hollow shell-shell structure having excellent performance is prepared. The material has the advantages of a simple preparation method and a short preparation cycle, and has opened up a new path for the research and development of catalytic materials for high-performance lithium-sulfur batteries.

[0030] The hollow shell-shell structured crystalline-amorphous heterogeneous P-CeO2 material prepared by the present invention consists of a highly crystalline CeO2 inner shell, an amorphous CePO4 outer shell and abundant active Ce-OP bonds. The highly crystalline CeO2 inner shell and grain boundary defects on the crystalline-amorphous heterogeneous structure can contribute to excellent electronic conduction performance, wherein: the highly crystalline CeO2 inner shell with high conductivity accelerates the electron transfer of the heterogeneous catalyst; the external amorphous CePO4 acts as a real catalytic shell, exposing abundant active Ce-OP bonds and optimizing the polysulfide conversion kinetics; the hollow structure can provide more adsorption and catalytic sites, and at the same time, the multi-shell structure can also inhibit the shuttling of polysulfides through a physical barrier. Therefore, using the P-CeO2 material as an intermediate layer catalyst of a lithium-sulfur battery can effectively improve the electrochemical performance of the lithium-sulfur battery.

[0031] The present invention utilizes a hollow shell-shell structure of crystalline-amorphous heterogeneous P-CeO2 to modify the lithium-sulfur battery separator, which can effectively inhibit the "shuttle effect" of polysulfides and reduce the corrosion of the lithium anode, thereby achieving high sulfur utilization. At 0.2C, the reversible initial capacity reaches 1358.6mAh·g -1 Moreover, at 0.2C, the capacity decay per cycle was only 0.0696% after 200 cycles; at 1C, the capacity decay per cycle was only 0.0422% after 600 cycles, showing excellent cycle stability. It can be seen that the crystalline-amorphous heterogeneous P-CeO2 modified diaphragm with a hollow shell-shell structure enables the Li-S battery to have better rate performance, cycle performance and higher specific capacity, thereby improving the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the XRD pattern of P-CeO2 synthesized in Example 1 of the present invention;

[0033] Figure 2 This is a SEM image of P-CeO2 synthesized in Example 1 of the present invention;

[0034] Figure 3 This is a TEM image of P-CeO2 synthesized in Example 1 of the present invention;

[0035] Figure 4The rate performance of Li-S batteries assembled from the crystalline-amorphous heterogeneous P-CeO2-modified lithium-sulfur battery separator and the commercial separator of the hollow shell-shell structure synthesized in Example 1 of the present invention;

[0036] Figure 5 The Li-S battery assembled with the hollow shell-shell structured crystalline-amorphous heterogeneous P-CeO2 modified lithium-sulfur battery separator and the commercial separator synthesized in Example 1 of the present invention has a high conductivity at 0.1 mV s -1 CV curve at a rate of;

[0037] Figure 6 The cycle performance diagram of Li-S battery assembled with the crystalline-amorphous heterogeneous P-CeO2 modified lithium-sulfur battery separator and the commercial separator of the hollow shell-shell structure synthesized in Example 1 of the present invention at a current density of 0.2C;

[0038] Figure 7 This is a cycling performance diagram of a Li-S battery assembled with a crystalline-amorphous heterogeneous P-CeO2-modified lithium-sulfur battery separator with a hollow shell-shell structure synthesized in Example 1 of the present invention and a commercial separator at a current density of 1C. DETAILED DESCRIPTION

[0039] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0040] Example 1

[0041] Step 1, ultrapure water and anhydrous ethanol are mixed in a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 70° C., 2 g of Cu2SO4·5H2O is first dissolved in 240 mL of ethanol solution, and then 20 mL of ethylene glycol is added, stirred for 40 min, and then 10 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 6 g of ascorbic acid powder is added to 30 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0042] Step 2: Dissolve 20 g of polyvinylpyrrolidone PVP in 600 mL of 50% ethanol solution, add 300 mg of CeCl3·7H2O, and after it is dissolved, add 500 mg of Cu2O, stir at room temperature with a magnetic stirrer for 30 min to obtain a brick red solution;

[0043] Step 3, 200 mL of 1 M sodium thiosulfate solution was added dropwise to the brick red solution, and the solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 hour, and then aged for 12 hours. The solid was separated by centrifugation, and then the solid was washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60°C for 12 hours to obtain a light yellow hollow CeO2 powder;

[0044] Step 4, weighing hollow CeO2 powder and NaH2PO2·H2O in a mass ratio of 1:20 and placing them at both ends of a porcelain boat respectively, placing the porcelain boat into a tube furnace, and heating from room temperature to 400°C at a heating rate of 2°C / min under an argon atmosphere, and keeping the temperature for 4 hours to obtain an intermediate product, which is recorded as P-CeO2-1;

[0045] Step 5. Weigh the intermediate product and NaH2PO2·H2O in a mass ratio of 1:20 and place them at both ends of a porcelain boat respectively. Put the porcelain boat into a tubular furnace. Under an argon atmosphere, heat the temperature from room temperature to 400°C at a heating rate of 2°C / min and keep it warm for 4 hours to obtain a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure, recorded as P-CeO2-2.

[0046] like Figure 1 As shown in the figure, the XRD spectrum of the crystalline-amorphous heterogeneous P-CeO2 with hollow shell-shell structure prepared in Example 1 is consistent with the standard spectrum of CeO2 and CePO4. Figure 1 However, its characteristic peak shifted slightly negatively, indicating that P atoms were successfully doped and formed Ce-PO bonds. After two phosphating treatments, the main diffraction peak became weaker and broader, indicating that the grain size and crystallinity of CeO2 were reduced after P doping.

[0047] like Figure 2 As shown, the crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure prepared in Example 1 is a hollow structure sphere with a regular shape and a relatively uniform size.

[0048] like Figure 3 As shown, the particle size of the crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure prepared in Example 1 is about 600 nm.

[0049] Example 2

[0050] Step 1, ultrapure water and anhydrous ethanol are mixed according to a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 70° C., 1.5 g of Cu2SO4·5H2O is first dissolved in 100 mL of ethanol solution, and then 10 mL of ethylene glycol is added, stirred for 40 min, and then 5 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 3 g of ascorbic acid powder is added to 30 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0051] Step 2: Dissolve 10 g of polyvinylpyrrolidone PVP in 600 mL of 50% ethanol solution, add 400 mg of CeCl3·7H2O, and after it is dissolved, add 300 mg of Cu2O, stir at room temperature with a magnetic stirrer for 30 min to obtain a brick red solution;

[0052] Step 3, 200 mL of 1 M sodium thiosulfate solution was added dropwise to the brick red solution, and the solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 hour, and then aged for 12 hours. The solid was separated by centrifugation, and then the solid was washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60°C for 12 hours to obtain a light yellow hollow CeO2 powder;

[0053] Step 4, weighing hollow CeO2 powder and NaH2PO2·H2O in a mass ratio of 1:20 and placing them at both ends of a porcelain boat respectively, placing the porcelain boat into a tube furnace, and heating from room temperature to 300°C at a heating rate of 2°C / min under an argon atmosphere, and keeping the temperature for 2h to obtain an intermediate product, which is recorded as P-CeO2-1;

[0054] Step 5. Weigh the intermediate product and NaH2PO2·H2O in a mass ratio of 1:20 and place them at both ends of a porcelain boat respectively. Put the porcelain boat into a tubular furnace. Under an argon atmosphere, heat the temperature from room temperature to 300°C at a heating rate of 2°C / min and keep it warm for 2h to obtain a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure, recorded as P-CeO2-2.

[0055] Example 3

[0056] Step 1, ultrapure water and anhydrous ethanol are mixed according to a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 80° C., 2.5 g of Cu2SO4·5H2O is first dissolved in 200 mL of ethanol solution, and then 15 mL of ethylene glycol is added, stirred for 40 min, and then 7.5 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 5 g of ascorbic acid powder is added to 40 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0057] Step 2: Dissolve 40 g of polyvinylpyrrolidone PVP in 700 mL of 50% ethanol solution, add 400 mg of CeCl3·7H2O, and after it is dissolved, add 400 mg of Cu2O, stir at room temperature with a magnetic stirrer for 30 min to obtain a brick red solution;

[0058] Step 3, 300 mL of 1 M sodium thiosulfate solution was added dropwise to the brick red solution, and the solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 hour, and then aged for 12 hours. The solid was separated by centrifugation, and then the solid was washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C. and dried for 12 hours to obtain a light yellow hollow CeO2 powder;

[0059] Step 4, weighing hollow CeO2 powder and NaH2PO2·H2O in a mass ratio of 1:20 and placing them at both ends of a porcelain boat respectively, placing the porcelain boat into a tube furnace, and heating from room temperature to 600°C at a heating rate of 2°C / min under an argon atmosphere, and keeping the temperature for 5 hours to obtain an intermediate product, which is recorded as P-CeO2-1;

[0060] Step 5. Weigh the intermediate product and NaH2PO2·H2O in a mass ratio of 1:20 and place them at both ends of a porcelain boat respectively. Put the porcelain boat into a tubular furnace. Under an argon atmosphere, heat the temperature from room temperature to 600°C at a heating rate of 2°C / min and keep it warm for 5 hours to obtain a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure, recorded as P-CeO2-2.

[0061] Example 4

[0062] Step 1, ultrapure water and anhydrous ethanol are mixed in a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 60° C., 1 g of Cu2SO4·5H2O is first dissolved in 100 mL of ethanol solution, and then 10 mL of ethylene glycol is added, stirred for 40 min, and then 10 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 8 g of ascorbic acid powder is added to 30 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0063] Step 2: Dissolve 25 g of polyvinylpyrrolidone PVP in 600 mL of 50% ethanol solution, add 500 mg of CeCl3·7H2O, and after it is dissolved, add 300 mg of Cu2O, stir at room temperature with a magnetic stirrer for 30 min to obtain a brick red solution;

[0064] Step 3, 400 mL of 1 M sodium thiosulfate solution was added dropwise to the brick-red solution, and the solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 hour, and then aged for 12 hours. The solid was separated by centrifugation, and then the solid was washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C. and dried for 12 hours to obtain a light yellow hollow CeO2 powder;

[0065] Step 4, weighing hollow CeO2 powder and NaH2PO2·H2O in a mass ratio of 1:20 and placing them at both ends of a porcelain boat respectively, placing the porcelain boat into a tube furnace, and heating from room temperature to 600°C at a heating rate of 2°C / min under an argon atmosphere, and keeping the temperature for 3 hours to obtain an intermediate product, which is recorded as P-CeO2-1;

[0066] Step 5. Weigh the intermediate product and NaH2PO2·H2O in a mass ratio of 1:20 and place them at both ends of a porcelain boat respectively. Put the porcelain boat into a tubular furnace. Under an argon atmosphere, heat the temperature from room temperature to 600°C at a heating rate of 2°C / min and keep it warm for 3 hours to obtain a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure, recorded as P-CeO2-2.

[0067] Example 5

[0068] Step 1, ultrapure water and anhydrous ethanol are mixed in a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 60° C., 3 g of Cu2SO4·5H2O is first dissolved in 200 mL of ethanol solution, and then 20 mL of ethylene glycol is added, stirred for 40 min, and then 15 mL of 2M NaOH solution is added dropwise, stirred for 40 min, to obtain a black solution; 10 g of ascorbic acid powder is added to 40 mL of ultrapure water, stirred for 40 min, to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, stirred for 40 min at room temperature, then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0069] Step 2: Dissolve 30 g of polyvinyl pyrrolidone PVP in 800 mL of 50% ethanol solution, add 600 mg of CeCl3·7H2O, and after it is dissolved, add 600 mg of Cu2O, stir at room temperature with a magnetic stirrer for 30 min to obtain a brick red solution;

[0070] Step 3, 200 mL of 1 M sodium thiosulfate solution was added dropwise to the brick red solution, and the solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 hour, and then aged for 12 hours. The solid was separated by centrifugation, and then the solid was washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60°C for 12 hours to obtain a light yellow hollow CeO2 powder;

[0071] Step 4, weighing hollow CeO2 powder and NaH2PO2·H2O in a mass ratio of 1:20 and placing them at both ends of a porcelain boat respectively, placing the porcelain boat into a tube furnace, and heating from room temperature to 300°C at a heating rate of 2°C / min under an argon atmosphere, and keeping the temperature for 3 hours to obtain an intermediate product, which is recorded as P-CeO2-1;

[0072] Step 5. Weigh the intermediate product and NaH2PO2·H2O in a mass ratio of 1:20 and place them at both ends of a porcelain boat respectively. Put the porcelain boat into a tubular furnace. Under an argon atmosphere, heat the temperature from room temperature to 300°C at a heating rate of 2°C / min and keep it warm for 3 hours to obtain a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure, recorded as P-CeO2-2.

[0073] Example 6

[0074] Step 1, ultrapure water and anhydrous ethanol are mixed in a volume ratio of 2:1 to obtain an ethanol solution; in a water bath at 70°C, 3.5 g of Cu2SO4·5H2O is first dissolved in 250 mL of ethanol solution, 30 mL of ethylene glycol is added, and the mixture is stirred for 40 min, and then 16 mL of 2M NaOH solution is added dropwise, and the mixture is stirred for 40 min to obtain a black solution; 10 g of ascorbic acid powder is added to 45 mL of ultrapure water, and the mixture is stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0075] Step 2: Dissolve 40 g of polyvinylpyrrolidone PVP in 600 mL of 50% ethanol solution, add 600 mg of CeCl3·7H2O, and after it is dissolved, add 380 mg of Cu2O, stir at room temperature with a magnetic stirrer for 30 min to obtain a brick red solution;

[0076] Step 3, 400 mL of 1 M sodium thiosulfate solution was added dropwise to the brick-red solution, and the solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 hour, and then aged for 12 hours. The solid was separated by centrifugation, and then the solid was washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C. and dried for 12 hours to obtain a light yellow hollow CeO2 powder;

[0077] Step 4, weighing hollow CeO2 powder and NaH2PO2·H2O in a mass ratio of 1:20 and placing them at both ends of a porcelain boat respectively, placing the porcelain boat into a tube furnace, and heating from room temperature to 400°C at a heating rate of 2°C / min under an argon atmosphere, and keeping the temperature for 4 hours to obtain an intermediate product, which is recorded as P-CeO2-1;

[0078] Step 5. Weigh the intermediate product and NaH2PO2·H2O in a mass ratio of 1:20 and place them at both ends of a porcelain boat respectively. Put the porcelain boat into a tubular furnace. Under an argon atmosphere, heat the temperature from room temperature to 400°C at a heating rate of 2°C / min and keep it warm for 4 hours to obtain a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure, recorded as P-CeO2-2.

[0079] Example 7

[0080] Step 1, ultrapure water and anhydrous ethanol are mixed according to a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 80° C., 4 g of Cu2SO4·5H2O is first dissolved in 300 mL of ethanol solution, and then 30 mL of ethylene glycol is added, stirred for 40 min, and then 18 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 9 g of ascorbic acid powder is added to 35 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0081] Step 2: Dissolve 10 g of polyvinylpyrrolidone PVP in 800 mL of 50% ethanol solution, add 300 mg of CeCl3·7H2O, and after it is dissolved, add 450 mg of Cu2O, stir at room temperature with a magnetic stirrer for 30 min to obtain a brick red solution;

[0082] Step 3, 300 mL of 1 M sodium thiosulfate solution was added dropwise to the brick red solution, and the solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 hour, and then aged for 12 hours. The solid was separated by centrifugation, and then the solid was washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C. and dried for 12 hours to obtain a light yellow hollow CeO2 powder;

[0083] Step 4, weighing hollow CeO2 powder and NaH2PO2·H2O in a mass ratio of 1:20 and placing them at both ends of a porcelain boat respectively, placing the porcelain boat into a tube furnace, and heating from room temperature to 500°C at a heating rate of 2°C / min under an argon atmosphere, and keeping the temperature for 2h to obtain an intermediate product, which is recorded as P-CeO2-1;

[0084] Step 5. Weigh the intermediate product and NaH2PO2·H2O in a mass ratio of 1:20 and place them at both ends of a porcelain boat respectively. Put the porcelain boat into a tubular furnace. Under an argon atmosphere, heat the temperature from room temperature to 500°C at a heating rate of 2°C / min and keep it warm for 2 h to obtain a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure, recorded as P-CeO2-2.

[0085] Example 8

[0086] Step 1, ultrapure water and anhydrous ethanol are mixed in a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 60° C., 1 g of Cu2SO4·5H2O is first dissolved in 150 mL of ethanol solution, and then 15 mL of ethylene glycol is added, stirred for 40 min, and then 15 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 6 g of ascorbic acid powder is added to 50 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0087] Step 2: Dissolve 30 g of polyvinyl pyrrolidone PVP in 800 mL of 50% ethanol solution, add 350 mg of CeCl3·7H2O, and after it is dissolved, add 600 mg of Cu2O, stir at room temperature with a magnetic stirrer for 30 min to obtain a brick red solution;

[0088] Step 3, 300 mL of 1 M sodium thiosulfate solution was added dropwise to the brick red solution, and the solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 hour, and then aged for 12 hours. The solid was separated by centrifugation, and then the solid was washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C. and dried for 12 hours to obtain a light yellow hollow CeO2 powder;

[0089] Step 4, weighing hollow CeO2 powder and NaH2PO2·H2O in a mass ratio of 1:20 and placing them at both ends of a porcelain boat respectively, placing the porcelain boat into a tube furnace, and heating from room temperature to 450°C at a heating rate of 2°C / min under an argon atmosphere, and keeping the temperature for 2h to obtain an intermediate product, which is recorded as P-CeO2-1;

[0090] Step 5. Weigh the intermediate product and NaH2PO2·H2O in a mass ratio of 1:20 and place them at both ends of a porcelain boat respectively. Put the porcelain boat into a tubular furnace. Under an argon atmosphere, heat the temperature from room temperature to 450°C at a heating rate of 2°C / min and keep it warm for 2 h to obtain a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure, recorded as P-CeO2-2.

[0091] Example 9

[0092] Step 1, ultrapure water and anhydrous ethanol are mixed according to a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 50° C., 2.5 g of Cu2SO4·5H2O is first dissolved in 200 mL of ethanol solution, and then 20 mL of ethylene glycol is added, stirred for 40 min, and then 12.5 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 6.5 g of ascorbic acid powder is added to 45 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0093] Step 2: Dissolve 15 g of polyvinylpyrrolidone PVP in 700 mL of 50% ethanol solution, add 400 mg of CeCl3·7H2O, and after it is dissolved, add 500 mg of Cu2O, stir at room temperature with a magnetic stirrer for 30 min to obtain a brick red solution;

[0094] Step 3, 300 mL of 1 M sodium thiosulfate solution was added dropwise to the brick red solution, and the solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 hour, and then aged for 12 hours. The solid was separated by centrifugation, and then the solid was washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C. and dried for 12 hours to obtain a light yellow hollow CeO2 powder;

[0095] Step 4, weighing hollow CeO2 powder and NaH2PO2·H2O in a mass ratio of 1:20 and placing them at both ends of a porcelain boat respectively, placing the porcelain boat into a tube furnace, and heating from room temperature to 500°C at a heating rate of 2°C / min under an argon atmosphere, and keeping the temperature for 4 hours to obtain an intermediate product, which is recorded as P-CeO2-1;

[0096] Step 5. Weigh the intermediate product and NaH2PO2·H2O in a mass ratio of 1:20 and place them at both ends of a porcelain boat respectively. Put the porcelain boat into a tubular furnace. Under an argon atmosphere, heat the temperature from room temperature to 500°C at a heating rate of 2°C / min and keep it warm for 4 hours to obtain a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure, recorded as P-CeO2-2.

[0097] Example 10

[0098] Step 1, ultrapure water and anhydrous ethanol are mixed in a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 80° C., 3 g of Cu2SO4·5H2O is first dissolved in 250 mL of ethanol solution, and then 30 mL of ethylene glycol is added, stirred for 40 min, and then 20 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 10 g of ascorbic acid powder is added to 50 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0099] Step 2: Dissolve 40 g of polyvinyl pyrrolidone PVP in 700 mL of 50% ethanol solution, add 450 mg of CeCl3·7H2O, and after it is dissolved, add 600 mg of Cu2O, stir at room temperature with a magnetic stirrer for 30 min to obtain a brick red solution;

[0100] Step 3, 350mL of 1M sodium thiosulfate solution was added dropwise to the brick-red solution, and the solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 hour, and then aged for 12 hours. The solid was separated by centrifugation, and then the solid was washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60°C for 12 hours to obtain a light yellow hollow CeO2 powder;

[0101] Step 4, weighing hollow CeO2 powder and NaH2PO2·H2O in a mass ratio of 1:20 and placing them at both ends of a porcelain boat respectively, placing the porcelain boat into a tube furnace, and heating from room temperature to 500°C at a heating rate of 2°C / min under an argon atmosphere, and keeping the temperature for 4 hours to obtain an intermediate product, which is recorded as P-CeO2-1;

[0102] Step 5. Weigh the intermediate product and NaH2PO2·H2O in a mass ratio of 1:20 and place them at both ends of a porcelain boat respectively. Put the porcelain boat into a tubular furnace. Under an argon atmosphere, heat the temperature from room temperature to 500°C at a heating rate of 2°C / min and keep it warm for 4 hours to obtain a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure, recorded as P-CeO2-2.

[0103] Application Example 1

[0104] The hollow shell-shell structured crystalline-amorphous heterogeneous P-CeO2-1, acetylene black and PVDF prepared in Example 1 were weighed and mixed in a mass ratio of 8:1:1, and then 10 drops of NMP were added and stirred to obtain a uniform slurry. The slurry was evenly coated on the surface of a commercial polypropylene separator for a Li-S battery and dried to obtain a hollow shell-shell structured crystalline-amorphous heterogeneous P-CeO2-1 modified lithium-sulfur battery separator.

[0105] Application Example 2

[0106] The hollow shell-shell structured crystalline-amorphous heterogeneous P-CeO2-2, acetylene black and PVDF prepared in Example 1 were weighed in a mass ratio of 8:1:1, mixed and ground, and 10 drops of NMP were added and stirred to obtain a uniform slurry. The slurry was evenly coated on the surface of a commercial polypropylene separator for a Li-S battery and dried to obtain a hollow shell-shell structured crystalline-amorphous heterogeneous P-CeO2-2 modified lithium-sulfur battery separator.

[0107] With MWCNTs / S as the positive electrode, metallic lithium as the negative electrode, 1.0M LiTFSI in DME:DOL=1:1Vol%with 1.0%LiNO3 solution as the electrolyte, commercial polypropylene separator pp, hollow shell-shell structure crystalline-amorphous heterogeneous P-CeO2-1 modified lithium-sulfur battery separator and hollow shell-shell structure crystalline-amorphous heterogeneous P-CeO2-2 modified lithium-sulfur battery separator were used as lithium-sulfur battery separators, and lithium-sulfur batteries were assembled in an argon-filled glove box. The results of the electrochemical performance test are as follows:

[0108] The rate performance of the assembled Li-S battery at current densities of 0.2C, 0.5C, 1C, 2C, 3C and 5C was tested using the LAND CT 2001A battery testing system. Figure 4 As shown in the figure, the discharge capacities of Li-S assembled by hollow shell-shell structured crystalline-amorphous heterogeneous P-CeO2-2 modified lithium-sulfur battery separators are 1358.6 mAh·g -1 、1194.1mAh·g -1 、1056.2mAh·g -1 、937.5mAh·g -1 、869.0mAh·g -1 and 802.8mAh·g -1 The discharge capacities of Li-S assembled by hollow shell-shell structured crystalline-amorphous heterogeneous P-CeO2-1 modified lithium-sulfur battery separators are 1168.5 mAh·g -1 、999.2mAh·g -1 、882.1mAh·g -1 、773.9mAh·g -1、710.0mAh·g -1 and 633.0mAh g -1 The discharge capacity of Li-S assembled with commercial polypropylene separator pp is 931.5 mAh g -1 、809.4mAh·g -1 、698.0mAh·g -1 、613.0mAh·g -1 、570.9mAh·g -1 and 495.0mAh g -1 ; By comparison, it was found that the crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure prepared by two phosphating steps in Example 1 can improve the rate performance of lithium-sulfur batteries.

[0109] like Figure 5 As shown, at 0.1mV s -1 Under these conditions, the peak current of the lithium-sulfur battery assembled with the P-CeO2-2 modified membrane at each redox peak is higher than that of the lithium-sulfur battery assembled with the P-CeO2-1 modified membrane and the PP membrane, which indicates that the P-CeO2 prepared by the second phosphating in Example 1 can give the lithium battery higher redox activity.

[0110] like Figure 6 and Figure 7 The long-life cycle stability of different lithium-sulfur batteries at current densities of 0.2 and 1C are demonstrated respectively. Among them, the lithium-sulfur battery assembled with the P-CeO2-2 modified diaphragm is cycled 200 times at 0.2C, and the capacity decay per cycle is only 0.0696%; at 1C, it is cycled 600 times, and the capacity decay per cycle is only 0.0422%, indicating that the P-CeO2 prepared by two phosphating in Example 1 has the synergistic effect of efficient catalysis and strong adsorption, which improves the cycle stability of the lithium-sulfur battery and the higher sulfur utilization rate.

Claims

1. A method for preparing a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure, characterized in that: The steps include: Step 1: Dissolve 10-40 g of polyvinyl pyrrolidone in 600-800 mL of 50% ethanol solution, add 300-600 mg of CeCl3·7H2O, and after it is dissolved, add 300-600 mg of Cu2O, stir at room temperature, and obtain a brick red solution; Step 2, 200-400 mL of 1M sodium thiosulfate solution was added dropwise to the brick-red solution to obtain a light yellow solution, which was stirred at room temperature, and then allowed to stand for aging, centrifuged, washed and vacuum dried in sequence to obtain a light yellow hollow CeO2 powder; Step 3, weighing hollow CeO2 powder and NaH2PO2·H2O in a mass ratio of 1:20 and placing them at both ends of a porcelain boat respectively, placing the porcelain boat into a tube furnace, and heating from room temperature to 300-600°C at a heating rate of 2°C / min under an argon atmosphere, and keeping the temperature for 2-5h to obtain an intermediate product; Step 4. Weigh the intermediate product and NaH2PO2·H2O in a mass ratio of 1:20 and place them at both ends of a porcelain boat respectively. Put the porcelain boat into a tubular furnace. In an argon atmosphere, heat the temperature from room temperature to 300-600°C at a heating rate of 2°C / min and keep it warm for 2-5h to obtain a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure.

2. The method for preparing the crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure according to claim 1, characterized in that: The Cu2O in step 1 is prepared by the following method: Step 1.1, mixing ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution; Step 1.2, in a water bath at 50-80°C, first dissolve 1-4 g of Cu2SO4·5H2O in 100-300 mL of the ethanol solution prepared in step 1.1, then add 10-30 mL of ethylene glycol, stir for 40 min, then add 5-20 mL of 2M NaOH solution dropwise, stir for 40 min, to obtain a black solution; Step 1.3, add 3-10 g of ascorbic acid powder into 30-50 mL of ultrapure water and stir for 40 min to obtain an ascorbic acid solution; Step 1.4: Add ascorbic acid solution dropwise to the black solution to obtain a brick-red solution. Stir the solution at room temperature for 40 min, let it stand for 3 h, and then filter, wash and vacuum dry in sequence to obtain brick-red Cu2O.

3. The method for preparing the crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure according to claim 1, characterized in that: The stirring in step 1 is carried out by using a magnetic stirrer for 30 minutes.

4. The method for preparing the crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure according to claim 1, characterized in that: The stirring time of step 2 is 1 h.

5. The method for preparing the crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure according to claim 1, characterized in that: The standing aging time in step 2 is 12 hours.

6. The method for preparing the crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure according to claim 1, characterized in that: The washing in step 2 is performed by alternately washing with deionized water and anhydrous ethanol for 3 times.

7. The method for preparing the crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure according to claim 1, characterized in that: The vacuum drying in step 2 is carried out in a vacuum drying oven at 60° C. for 12 h.

8. A crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure prepared by the method of claim 1.

9. Use of the crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure as claimed in claim 8 in a lithium-sulfur battery separator.

10. The use of the hollow shell-shell structured crystalline-amorphous heterogeneous P-CeO2 in a lithium-sulfur battery separator according to claim 9, characterized in that: The steps include: The crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure, acetylene black and PVDF were weighed and mixed in a mass ratio of 8:1:1, and then NMP was added dropwise and stirred to obtain a uniform slurry. The slurry was evenly coated on the surface of a commercial polypropylene separator and dried to obtain a crystalline-amorphous heterogeneous P-CeO2 with a hollow shell-shell structure modified lithium-sulfur battery separator.